A Note on \(q\)-Sălăgean Type Functions - Annapoorna, S.; Dileep, L. (Journal of Informatics and Mathematical Sciences, 2025)
In the present paper, we define certain classes of analytic function in the open disc by using the generalized linear operator \(D_λ,δ^n\) with help of \(q\) calculus. For functions belonging to these classes we provide coefficient inequalities, distortion theorem.